Case report: Congenital mitral and tricuspid valve insufficiency in a patient with Axenfeld-Rieger syndrome - Feng, Jingwei; Wang, Yingjiao; Cheng, Shiyu; Liu, Zishuo; Lan, Ling; Miao, Qi; Zhang, Chaoji (Frontiers in Cardiovascular Medicine, 2022)
Axenfeld-Rieger syndrome (ARS) is an autosomal dominant disorder that is primarily due to disruption of the development of neural crest cells. The onset of associated symptoms in both eyes accompanied by extraocular developmental defects is referred to as ARS. Cardiac defects associated with ARS have been reported, but the extent of the cardiac defects has yet to be defined. We report a case of a 17-year-old girl with ARS with typical facial malformations and severe mitral and tricuspid valve insufficiency. The patient was diagnosed with secondary glaucoma detected on ophthalmologic examination. Echocardiography showed severe mitral and tricuspid valve insufficiency. This case provides further evidence of the association of ARS with cardiac malformations and extends the reported range of cardiac malformations in patients with ARS.